Respuesta :

the expression is 27a^3   or (3a)^3

For this case we have the following expression:

[tex]27 * a * a * a[/tex]

By definition, by ownership of the power:

In the multiplication, if we have the same base the exponents are added, for example:

[tex]A (x * x * x) = Ax^{(1 + 1 + 1)}= Ax ^ 3[/tex]

Rewriting the given expression we have:

[tex](3 * 3 * 3) (a * a * a) =[/tex]

[tex](3^ {(1 + 1 + 1)})*(a^ {(1 + 1 + 1)}) =[/tex]

[tex]3 ^ 3 * a ^ 3 =[/tex]

[tex](3a) ^ 3[/tex]

Answer:

Rewriting the given expression we have:

[tex](3a) ^ 3[/tex]